Evaluasi Kerentanan Keamanan Pada Perangkat Iot: Studi Kasus Pada Smart home - Cahyo Utomo, Ihsan (The Indonesian Journal of Computer Science, 2024)
The presence of the Internet of things (IoT) has changed the way of interacting with electronic devices in everyday environments. One implementation of IoT is a smart home, where the automation of various devices in the home is connected online to increase comfort and efficiency. However, in implementing a smart home there are challenges on the security side. Because smart home applications are connected to the internet, they are vulnerable to security attacks such as access rights attacks, viruses and malware. This research discusses the need for security evaluation on smart home devices, this is because the characteristics of smart homes are heterogeneous, dynamic and connected to the internet network, so they have potential vulnerabilities from cyber attacks. The aim of this research is to evaluate security vulnerabilities in IoT devices in the context of a smart home. Through case studies covering various devices commonly found in smart homes, one of which is the potential vulnerabilities and security risks associated with the use of IoT devices. The research methods used include penetration testing, vulnerability analysis, and evaluation of implemented security policies. The results of this research can provide an overview of potential security risks to IoT devices in smart homes and help develop stronger protection models to face the growing security challenges in IoT applications.